Muhammadiyah’s Moderation Stance in the 2019 General Election: Critical Views from Within - Haedar Nashir; Zuly Qodir; Achmad Nurmandi; Hasse Jubba; Mega Hidayati (Al-Jami'ah Research Centre, 2019)
This study focuses on the way in which Muhammadiyah, one of Indonesia’s largest Islamic organizations, stood in the 2019 General Election. Like its counterpart Nahdlatul Ulama, Muhammadiyah has marked the moderation of Islam in Indonesia, different from Islam elsewhere in the Middle East. Since its establishment, Muhammadiyah has urged its members not to join any specific political party, but rather to take a moderate position in political pragmatism and support patriotism in broader national interest. Likewise, in the 2019 election, Muhammadiyah did not organizationally support any candidates, citing its “middle way” approach. However, this study identifies a dualism in the political attitudes of Muhammadiyah’s elites. Even without official orders or prohibitions from the central leadership, some Muhammadiyah members got involved and carried their organization’s attributes to support certain candidates, resulting in political division within the organization. Some members of the organization took a clear political stance, whereas others remain neutral. This created tension within the organization in both elite and grass-root level. The main data for this study were collected through interviews, unstructured discussions, and focus group discussions with several Muhammadiyah elites.[Artikel ini melihat posisi yang diambil salah satu organisasi Islam terbesar di Indonesia, Muhammadiyah, dalam Pemilu 2019. Bersamaan dengan Nahdlatul Ulama, Muhammadiyah menjadi penanda moderasi Islam di Indonesia yang berbeda dengan Islam di tempat lain. Sejak didirikan, Muhammadiyah telah menandaskan untuk tidak berafiliasi dengan partai politik tertentu, tetapi mengambil posisi moderat dalam perpolitikan dan mendukung patriotisme demi kepentingan nasional yang lebih luas. Demikian juga, dalam Pemilu 2019, Muhammadiyah secara resmi tidak mendukung calon mana pun berdasarkan konsep “jalan tengah”. Namun, penelitian ini mengidentifikasi adanya dualisme dalam sikap politik para elit Muhammadiyah. Tidak adanya perintah atau larangan resmi dari pusat, banyak anggota Muhammadiyah yang membawa atribut organisasi dan terlibat aktivitas politik serta mendukung kandidat tertentu. Ini berakibat munculnya keterbelahan politik dalam Muhammadiyah. Beberapa anggota mengambil sikap politik yang jelas, sedangkan yang lain tetap netral. Ini menimbulkan ketegangan dalam organisasi, baik di tingkat elit maupun akar rumput. Data utama untuk penelitian ini dikumpulkan melalui wawancara, diskusi tidak terstruktur, dan diskusi kelompok terfokus dengan beberapa elit Muhammadiyah.]